Politics of Representation: construction and marketing of the new identities in the political mediaspace - Suárez Navaz, Liliana (Revista de Antropología Social, 2011)
This article explores some premilinary findings of the research on “Politics of Representation in the Transnational Migratory Field: Production, Distribution and Consumption of Media in Migratory Context” (CSO2008-03022). From an initial theoretical reflection on the main challenges Anthropology finds in the globalization context, we describe and analyze the recent burst of mass media oriented towards immigrant population in Spain. I delve into the analysis of content of these media, based on a quantitative and qualitative research, comparing briefly the results with dominant media. I analyze the construction of the “news” in migratory, transnational and cultural dimensions, exploring the emergence of a new ethnocultural category new in Spain, that of “Latin@s”. I finally offer three Ideal Types of the articulation of Latin American journalist with their audiences and their sociological grass roots organizations and communities: instrumental, clientelist, and organic. I then conclude through a series of considerations about the importance of the ethnographic work on the public space through a transnational perspective that deals with political communication processes in the new mediaspaces which shape our social world as citizens.
Keywords: International migration; public space; political anthropology of media and journalism; ethnicity; etnogenesis